Peranan Sistem Absensi dalam Meningkatkan Disiplin Kerja pada Pegawai Fraksi DPRD Provinsi Sumatera Utara - Devi Damayanti; Laylan Syafina (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The aim of this research is to improve discipline, especially in terms of attendance given to employees at the Gerindra Faction Office in North Sumatra. Using descriptive qualitative research. The data used comes from interviews with direct questions and answers to the parties involved in the research. The research data will determine the type of information system needed. Based on the research results, it is hoped that the presence of an attendance system will help employees improve work discipline and arrive at work on time, complete work more quickly and reduce the occurrence of social jealousy between fellow employees. One way to improve discipline in the workplace is to provide sanctions and warnings to employees who break the rules, which in turn makes employees more disciplined and better able to avoid subsequent violations. Thus, increasing monitoring of employee actions will lead to increased discipline and overall levels of productivity in the workplace.